2011
DOI: 10.1007/s11274-011-0692-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of alcohols on bacterial cellulose production by Acetobacter xylinum 186

Abstract: To improve the yield of cellulose production in bacteria, we investigated the stimulatory effects of six different alcohols during fermentation of Acetobacter xylinum 186. Our study showed that after static fermentation at 30°C for 6 days, bacterial culture with 1.0% (v/v) of methanol added in the medium produced the highest bacterial cellulose (BC) yield at 103.5 mg/100 ml, which was 21.8% higher than the control group. Addition of 0.5% of ethylene glycol in the culture yielded 105.5 mg/100 ml BC, 24.1% highe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(22 citation statements)
references
References 16 publications
2
20
0
Order By: Relevance
“…Similarly, the addition of agar at a concentration of 0.6% in the stirred-tank reactor generated 11.6 g L − 1 of BC by Acetobacter xylinum BPR2001 [49]. In the present study, addition of 1% PEG 6000 as polymer additive in HS medium enhanced the BC yield as reported earlier [28,50].…”
Section: Discussionsupporting
confidence: 83%
“…Similarly, the addition of agar at a concentration of 0.6% in the stirred-tank reactor generated 11.6 g L − 1 of BC by Acetobacter xylinum BPR2001 [49]. In the present study, addition of 1% PEG 6000 as polymer additive in HS medium enhanced the BC yield as reported earlier [28,50].…”
Section: Discussionsupporting
confidence: 83%
“…It seems that butanol was a more suitable carbon source than ethanol for BC production by G. xylinus in the ABE fermentation wastewater. In other researches, both ethanol and butanol have been shown that could improve the BC yield (Yunoki et al 2004;Lu et al 2011).…”
Section: Metabolism Of Gluconacetobacter Xylinus In Abe Fermentation mentioning
confidence: 95%
“…More often, both ethanol and acetate are spiked in media to enhance BC production by improving adenosine triphosphate (ATP) production, which is responsible for energy supply in the tricarboxylic acid (TCA) cycle and sugar metabolisms. Specifically, these processes are achieved by promoting the activities of glucokinase and fructokinase for BC production and inhibiting the activities of gluconokinase and glucose-6-phosphate dehydrogenase in pentose phosphate metabolism for energy production [17,18,19,20,21,22].…”
Section: Introductionmentioning
confidence: 99%